A Framework for regional growth and development in CARICOM ([ ] [ ])
Takes into account the technical work undertaken in preparation of the Strategic Plan for Regional Economic Development (SPRED), basic elements of the Caribbean Sea Convergence Model as well as the proposals emanating from the World Bank and Inter-american Development (IDB) led initiatives to provide a contextual framework to inform the discussions among Head of Government on the future of CARICOM economies.
Keywords: CARICOM